2, 5-Bis(azulenyl)pyrrolo[3, 2-b]pyrroles – the key influence of the linkage position on the linear and nonlinear optical properties. Issue 10 (23rd February 2017) - Poronik, Yevgen M.; Mazur, Leszek M.; Samoć, Marek; Jacquemin, Denis; Gryko, Daniel T.
Abstract : Linking pyrrole[3, 2- b ]pyrrole core with azulene moieties leads to dyes possessing strong visible light absorption, no emission, and a two-photon absorption spectrum. Abstract : The first route towards pyrrolo[3, 2- b ]pyrroles containing two azulene moieties at positions 2 and 5 was developed. The key step of this approach is the three-step transformation of pyridine scaffolds into azulene via sequential N -arylation followed by ring-opening and a reaction with cyclopentadiene. The resulting quadrupolar acceptor–donor–acceptor compounds possess interesting optical properties such as bathochromically shifted absorption with the magnitude of the red-shift strongly dependent on the linkage position. Two-photon absorption of these functional dyes is markedly different from that of previously described pyrrolo[3, 2- b ]pyrroles. The experimental optical spectra were rationalized using time-dependent density functional theory calculations of both the linear and nonlinear optical properties.